Professional training of a future teacher of primary education in the context of the competent approach - Кізіцька, Т. І.; Юхно, Л. В. (Scientific notes of the pedagogical department, 2018)
The content and the meaning of the concepts «professional competence», «competent approach» are disclosed in the article. The peculiarities of the formation of professional competence of future teachers of primary education in the institutions of higher education in the context of the competent approach during double periods, practical training, events of methodical directions, individual work and research activity of the students are highlighted. The ways, based on work experience, how to bring students closer to the conditions of modern primary school, to intensify their pedagogical thinking, which helps to overcome the gap between theoretical knowledge and future professional pedagogical activity are described. Innovative educational technologies, in particular, informational-communicative and interactive technologies are also considered in the article because they help to form the personality of a future teacher, develop his/her creativity, culture, erudition. Considerable attention is paid to the use of multimedia accompaniments to double periods and extracurricular activities, audio and video materials, computer training programs, students’ projects, because projects are a compulsory element of the educational process in primary school. The types and themes of students’ projects are also presented. The importance of teaching practice for the qualitative training of future specialists in accordance with modern requirements, as well as various forms of students’ scientific-research works which help to form scientific outlook, the abilities and skills of scientific research and to develop the initiative, creative, scientific thinking and professional communication are shown. The effective forms of scientific-methodical work based on work experience and directed on the formation of professional competence, pedagogical skills of future teachers of primary education are presented. It is proved that the introduction of the competent approach in education requires refusing from the informational orientation in teaching process and transferring the emphasis from the mastering of normatively defined knowledge and skills on the formation and development of students’ ability to act practically and independently, to apply individual experiences and achievements in non-standard, creative, life situations.